Parts of model of information and safety systems - Pavol Tomasov; Karol Rastocny; Jiri Zahradnik (Communications - Scientific letters of the University of Zilina, 2000)
Modelling techniques for large and composite systems are chosen with regard to the expected result of modelling. For routine procedure of synthesis the empirical method is sufficient in most cases. System model with exact description of its attributes demands application of some theoretical conclusions. For information and safety systems a model derived from Information theory is selected. This model can then be specified with the help of the system and, eventually, circuit theory. In the presented paper two tools of Information theory apparatus for model system processing are described. They express information processing inequality and quantification of faults occurring by information manipulation.